Analisis Pengaruh Pendapatan Asli Daerah Terhadap Produk Domestik Regional Bruto Di Kabupaten Banggai Tahun 2013 – 2022: Analysis Of The Influence Of Local Real Income On Gross Regional Domestic Product In Banggai Regency In 2013 – 2022 - Husen, Sri Rahayu (Jurnal Ilmiah Produktif, 2024)
The problem in this study is how the influence of Regional Original Income on Gross Regional Domestic Product in Banggai Regency, with the aim of finding out the influence of Regional Original Income on Gross Regional Domestic Product in Banggai Regency. Qualitative data types. The analysis tool used is a simple linear regression using a ready-to-use program, namely the Excel application. Based on the regression coefficients shown, the equation Y = 2.708 + 93.59X was obtained. The correlation coefficient R = 0.879, means that the relationship between the regional Original Income variable and the Gross Regional Domestic Product in Banggai Regency is Very Strong. Based on the calculation of the Determination coefficient, it was obtained that the Regional Original Revenue variable (X) had a contribution to the Gross Regional Domestic Product Variable (Y) with a value of 0.773 or 77.3%. From the statistical test t, it was found that the tcount value was 5.223 and the ttable value was 1.812, this shows that the regional original income variable (X) has a significant effect on the Gross Regional Domestic Product (Y), in other words Ho is rejected and Ha is accepted.